Irrigation management of Punica granatum in the Sub-Middle São Francisco River Valley: Morphophysiological aspects. - Leal, Larissa de Sá Gomes; Marinho, Lígia Borges; Gertrudes Macário de; Maria Érica Pereira dos; Vagner Deniz Clemente; Aires, Eduardo Santana; Figueiredo Neto, Acácio (Comunicata Scientiae, 2024)
Water availability in arid and semi-arid areas has been a limiting factor to the expansion of agricultural production in several regions of the world. In this context, this research aimed to study the morphophysiological responses of pomegranate as a function of different irrigation depths in the Sub-Middle São Francisco River Valley (SSFV). The research was carried out in a commercial area located in Petrolina-PE, Brazil, with eight-year-old plants of lineage No. 12 of Embrapa Semi-Arid, spaced 4.0 x 2.0 m. Drip irrigation with a flow of 2.4 L h−1 emitter−1 was used every two days. The treatments consisted of D50 – continuous irrigation deficit with 50% ET0 replacement, D75 – continuous irrigation deficit with 75% ET0 replacement, D100 – continuous irrigation deficit with 100% ET0 replacement, and DF – farm irrigation. The experiment was conducted in randomized blocks with five replications. Plant height, cup diameter, number of flower buds, flowers, and fruits, relative chlorophyll content, free proline content in the leaves, gas exchange, water potential in the branch, and soil moisture were evaluated. The data were submitted for analysis of variance and regression at the 5% probability level, using the Sisvar program. We observed that the analyzed pomegranate can avoid excessive water loss to the atmosphere when subjected to water stress using different mechanisms. Moreover, the deficit of irrigation depths led to an anticipation and/or uniformity of flowering.